Medical journals in the Republic of Macedonia after the Second World War - Polenakovic, Momir; Danevska, Lenche (My University, 2011)
An attempt was made to retrospectively examine the medical journals published in the Republic of Macedonia since the Second World War. An analysis was made of the basic data concerning the journals, most of which are deposited in the Central Library of the Medical Faculty at the Ss. Cyril and Methodius University in Skopje, and a few deposited in the National and the St. Clement of Ohrid University Library in Skopje. Some journal-related data were obtained by searching the electronic databases (mainly Medline/PubMed, Hinari, Ebsco) and the Internet as a global system of network of networks. After the Second World War several attempts at publishing biomedical journals have been made in the Republic of Macedonia. The number of journals has increased especially in the last ten years. Only a few of them have a long-term publishing tradition. In fact, the only journal to maintain continuity in publishing until today is the Macedonian Medical Review, that has been published regularly since 1946 until today. It is an official publication of the Macedonian Medical Society. The Annual of the Medical Faculty in Skopje was published from 1954 to 1997 under this name, and in 1997 it was renamed the Macedonian Journal of Medicine. There was an interruption in its publishing in 1999 and 2000 and it was regularly published until 2007, after which its publication ceased once more. In addition to these two journals, other medicine-related journals that have been published in the Republic of Macedonia (some of them, however, irregularly or they have ceased publication) are Acta Morphologica (since 2004); Physioacta (since 2007); Paediatrics Annual Review (since 1996); Epilepsy (since 1997); Acta Ortopedica et Traumatologica Macedonia (since 1999); MJMS-Macedonian Journal of Medical Sciences (since 2008); Prilozi Macedonian Academy of Arts and Sciences (since 1969); Macedonian Dental Review (since 1977); Dental Review (since 2007); Macedonian Pharmaceutical Bulletin (since 1964); Macedonian Veterinary Review (since 1972); Archives of Public Health (since 2009); Medicus (since 2004); Vox Medici (since 1992); Social Medicine--Professional Journal for Public Health (since 2009); Journal of Special Education and Rehabilitation (since 1997); Balkan Journal of Medical Genetics (since 1998); BANTAO Journal (since 2003); Public Health--Journal for Health Education (1952-1986); Acta Chirurgica Iugoslavica (since 1954); Acta Chirurgica Macedonica (2001-2004); We You and Healthcare (since 2006); Newsletter-Health, Kavadartsi (1999); Medical Review--Professional Journal of the Medical Workers in Shtip (2001); Medicus--Information Newsletter of Public Health, General Hospital Shtip (2006); Medical Bulletin of the Health Service of the Skopje Army Region (1957-1987); Medical Spectrum--Professional Journal of Alkaloid--Skopje (1972-1981); Healthcare Newsletter, Kumanovo (1990-1996); Healthcare, Shtip (1979-1994); Healthcare Platform, Bitola (1975-1984); Journal with papers of the Society of Science and Art, Prilep; Healthcare Newsletter of the Medical Center Prilep (1975-1986); Healthcare Newsletter, Strumica (1978-1988); Contributions, a Journal of the Society of Science and Arts from Bitola; Doctors' Newspaper--Informative and educational newspaper of the Macedonian Medical Association (2010). A number of medical journals appear and after a short period of time disappear. The papers are mainly written in the Macedonian language, and none of the journals are currently indexed in Pub/Med, except for the Prilozi/Contributions of the Macedonian Academy of Sciences and Arts. In our opinion, to improve the quality of the published papers in the Macedonian journals, several goals have to be accomplished: better equipment and facilities in the hospitals, institutes and research centres that would yield better basic research and clinical trials; better basic education on how to write and publish scholarly/scientific papers, which has to be conducted at both undergraduate and postgraduate levels, along with lifelong learning; better peer-review processes; better editorial policy of the journals; compliance with international standards/uniform requirements for manuscripts submitted to biomedical journals; fostering the goals of the World Association of Medical Editors and European Association of Science Editors, etc. If these tasks and goals are realized, then we can build a solid ground to better present our medical results to the world.
Keywords: medical journals, Republic of Macedonia